S1‐1/RBM10: Multiplicity and cooperativity of nuclear localisation domains. (15th February 2013) - Xiao, Sheng‐Jun; Wang, Ling‐Yu; Kimura, Masatsugu; Kojima, Hirotada; Kunimoto, Hiroyuki; Nishiumi, Fumiko; Yamamoto, Naoki; Nishio, Koji; Fujimoto, Shunsuke; Kato, Takayuki; Kitagawa, Seiichi; Yamane, Hideo; et al.
Abstract Background information S1‐1, also called RBM10, is an RNA‐binding protein of 852 residues. An alteration of its activity causes TARP syndrome, a severe X‐linked disorder with pre‐ or post‐natal lethality in affected males. Its molecular function, although still largely unknown, has been suggested to be transcription and alternative splicing. In fact, S1‐1 localises in the nucleus in tissue cells and cultured cells. Results By deletion and substitution mutagenesis, a classical 17‐amino‐acid (aa) nuclear localisation sequence (NLS1) was identified at aa 743–759 in the C‐terminal region of S1‐1. NLS1 was bipartite, with its N‐terminal basic cluster weakly contributing to the NLS activity. S1‐1 contained two additional NLSs. One was in the aa 60–136 RNA recognition motif region (NLS2), and the other was a novel NLS motif sequence in the aa 481–540 octamer‐repeat (OCRE) region (NLS3). The OCRE is a domain known to be critical in splicing regulation, as shown with RBM5, a close homologue of RBM10 [Bonnal et al. (2008) Mol. Cell 32, 81–95]. The NLS activities were verified by expressing each DNA sequence linked to EGFP or a FLAG tag. These multiple NLSs acted cooperatively, and S1‐1 became completely cytoplasmic after the concomitant removal of all NLS domains. In some cell types, however, S1‐1 was partly cytoplasmic, suggesting that cellular localisation of S1‐1 is subjected to regulation. Conclusions The present results indicate that S1‐1 contains multiple NLSs that act cooperatively. Among them, the OCRE is a hitherto unreported NLS. The nuclear localisation of S1‐1 appears to be regulated under certain circumstances. We discuss these NLSs in relation to the biochemical processes they are involved in.